Effect of incorporation POFA in cement mortar and desired benefits: a review - Hamada, Hussein M.; Fadzil, Mat Yahaya; Khairunisa, Muthusamy; Humada, Ali Mahmood (IOP Publishing Ltd, 2019)
Palm oil fuel ash (POFA) is a by-product waste material more economical and environmentally friendly, resulted from production palm oil products. Lack of enough information on the advantages of POFA in the concrete production in various proportions was the main cause to select this work. This paper presents the advantages of POFA as a partial cement replacement in concrete production. This study recommends that researchers and academics should show more experimental works in order to illustrate the desired benefits from POFA as cement replacement, thus mitigate of environmental impacts.